Perkembangan Media Pembelajaran: Dari Media Konvensional hingga AI Generatif : Tinjauan Pedagogis dan Manajemen Pendidikan - Damar Ary Yahya; Nurul Abidatul Muthayyibah; Ghaida Diffa Syahida; Safira Maulidiya Supriyatna (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Advances in digital technology have brought about significant changes in various aspects of life, including education and school administration. Learning media play a central role in facilitating the comprehensive and effective delivery of educational content. Along with the rapid advancements in information and communication technology (ICT), learning media are no longer limited to conventional tools but are undergoing a radical transformation toward a digital ecosystem and the utilization of artificial intelligence (AI). This study aims to analyze the evolutionary trajectory of educational media from the conventional era to the era of Generative AI, as well as to examine its implications for pedagogical practices and educational management. The method used is a literature review with a qualitative approach, aggregating various reputable scientific sources from the past five years. The results of the study demonstrate that the evolution of media has shifted the educational paradigm from teacher-centered to learner-centered, positioning students as co-creators of knowledge. Generative AI offers revolutionary opportunities in the form of unlimited learning personalization and reduced administrative burdens for educators. However, its implementation requires strategic intervention from school management, particularly in Human Resource Management (HRM), to improve teachers’ digital literacy, establish strict academic Standard Operating Procedures (SOPs), and promote Project and oral performance assessments as concrete solutions to mitigate the threat of cognitive atrophy among students in the digital age.